Analysis of immune cell activation in patients with diabetes foot ulcer from the perspective of single cell - Lehoanganh Vu; Fei Xu; Ting Li; Qikai Hua; Xiaocong Kuang; Yongqiang Jiang; Yanfei Liang; Xing Niu; Yixuan Chen; Chengyu Huang; Weiliang Mo; Kejian Wang; et al. (European Journal of Medical Research)
Abstract Background Diabetes mellitus (DM) can cause severe complications, including diabetic foot ulcers (DFU). There is a significant gap in understanding the single-cell ecological atlas of DM and DFU tissues. Methods Single-cell RNA sequencing data were used to create a detailed single-cell ecological landscape of DM and DFU. Enrichment analysis identified pathways involved in cellular subpopulations, and pseudo-time analysis inferred cell development processes. A gene regulatory network explored the role of transcription factors in DFU progression, and a potential herbal drug-target gene interaction network was constructed. Results In the DFU group, immune cells were activated, with notable changes in several subpopulations. ATP5E was significantly overexpressed in Naive T cells, fibroblasts, endothelial cells, and CD8+ T cells in DM patients. Specific immune cell subsets, such as Naive T_RGCC, CTL_TYROBP_CL4, Mac_SLC40A1, and M1_CCL3L1, likely contribute to DFU formation through overactivation and proliferation, leading to tissue damage and ulcer exacerbation. Key genes TPP1, TLR4, and RIPK2 were identified, and 88 active ingredients in the herbal drug-target network showed strong correlations with these targets. Herbs like Angelica dahurica, Angelica sinensis, Boswellia carterii, liquorice, myrrh, and Semen armeniacae amarae were included. Conclusions This study offers insights into DM and DFU cytology. T cells in DFU are activated, attacking normal tissues and worsening tissue damage. The ATP5E gene may be related to the ecological remodeling of DM, and TPP1, TLR4, and RIPK2 are potential targets for DFU treatment.